Perceived Social Support among Psychiatric Outpatients: A Cross-Sectional Study in Indonesia - Sri Novitayani; Marthoenis Marthoenis; Martina Martina; Farah Dineva R; Rudi Alfiandi1 , Aiyub Aiyub (JLUMHS, 2024)
OBJECTIVE: This study aimed to determine the social support among psychiatric outpatients. METHODOLOGY: This cross-sectional study was conducted among 120 psychiatric outpatients who visited a psychiatric hospital in Banda Aceh, Indonesia. The inclusion criteria consist of a diagnosed schizophrenia by the psychiatrist, aged between 18 and 60 years old, scoring on the Brief Psychiatric Rating Scale (BPRS) less than 41, good communication, and willingness to participate in this study. Data collection includes the socio-demographic information of the respondents, a Brief Psychiatric Rating Scale, and a Multidimensional Scale of Social Support (MSPSS). Frequency and percentage were used to report the demographic data and social support levels. The Stata 13 statistical software was used to analyze the data. RESULTS: It was found that more than half of psychiatric outpatients have moderate social support (60%). CONCLUSION: It means that they have sufficient social help from family, friends, and significant others. However, social support from friends should be improved, as it was found to be among the lowest supports the patients obtained.